The global patient-reported outcomes for multiple sclerosis initiative: bridging the gap between clinical research and care – updates at the 2023 plenary event - Zaratin, Paola; Samadzadeh, Sara; Seferoğlu, Meral; Ricigliano, Vito; dos Santos Silva, Jonadab; Tunc, Abdulkadir; Brichetto, Giampaolo; Coetzee, Timothy; Helme, Anne; Khan, Usman; McBurney, Robert; Peryer, Guy; et al. (Frontiers in Neurology, 2024)
Significant advancements have been achieved in delineating the progress of the Global PROMS (PROMS) Initiative. The PROMS Initiative, a collaborative endeavor by the European Charcot Foundation and the Multiple Sclerosis International Federation, strives to amplify the influence of patient input on MS care and establish a cohesive perspective on Patient-Reported Outcomes (PROs) for diverse stakeholders. This initiative has established an expansive, participatory governance framework launching four dedicated working groups that have made substantive contributions to research, clinical management, eHealth, and healthcare system reform. The